TEG Platelet Mapping and Impedance Aggregometry to Predict Platelet Transfusion During Cardiopulmonary Bypass in Pediatric Patients - Barker, Erin E.; Saini, Arun; Gazit, Avihu Z.; Shea, Susan M.; Baltagi, Sirine; Gage, Brian F.; Spinella, Philip C. (Frontiers in Pediatrics, 2019)
Background: Cardiopulmonary bypass-related platelet dysfunction can increase the risk of intra- and post-operative bleeding in children undergoing cardiac surgery. More accurate laboratory tests that identify acquired platelet abnormalities could allow for rapid identification of patients at risk of bleeding and provide therapies that could reduce bleeding and platelet transfusions. We hypothesized that thromboelastography with platelet mapping (TEG-PM) and multiple electrode impedance aggregometry (MEIA) as functional measures of platelet function would predict who will require platelet transfusion. Our secondary hypothesis was that platelet aggregation at both arachidonic acid (AA) and adenosine diphosphate (ADP) receptors would correlate between TEG-PM and MEIA results. Methods: In this prospective study from August 2013 to December 2015, children from newborn to 5 years of age with congenital heart disease undergoing cardiopulmonary bypass had blood samples collected and analyzed at four time points: pre-bypass, post-bypass, post-operatively on arrival to the Cardiac Intensive Care Unit, and 24 hours after arrival. Results: Of the 44 patients analyzed, the 10 patients who received peri-operative platelet transfusion were significantly younger (p=0.05), had higher STAT (Society of Thoracic Surgeons-European Association for Cardio-Thoracic Surgery) Mortality Categories (p<0.002) and longer cardiopulmonary bypass times (p=0.02). In univariate analysis, four variables were associated with peri-operative platelet transfusion: pre-operative age (OR 0.95 (0.93, 0.98), p=0.03), cardiopulmonary bypass time (1.5 (1.31,1.68), p=0.008), STAT Mortality Category (3.64 (3.40,3.87), p<0.001), and TEG-PM ADP (0.79 (0.65,0.93), p=0.04). In the multivariate analysis, only STAT Mortality Category predicted platelet transfusion. TEG-PM and MEIA results correlated for the AA receptor at all 4 time points, but the same tests at the ADP receptors did not correlate. Conclusions: TEG-PM ADP may provide more clinically relevant information regarding platelet function compared to the MEIA at the ADP receptor in children requiring cardiopulmonary bypass. There was limited correlation between TEG-PM and MEIA results which raises a concern about the accuracy of these tests at the ADP receptor. Lower pre-operative TEG-PM ADP MA may predict intra-operative platelet transfusions; however, larger studies are needed to determine the utility of TEG-PM and MEIA in guiding platelet transfusions in this population.